Analysis of the effects of fabric reinforcement parameters on the mechanical properties of textile-based hybrid composites by full factorial experimental design method. (September 2018) - Sezgin, Hande; Berkalp, Omer B
In this study, the effect of some fabric reinforcement parameters (fabric direction, yarn type and stacking sequence) on the mechanical properties of textile based hybrid composites are analysed by using full factorial experimental design method. The analysis of the results is achieved by using Minitab 17 software program. One factor (fabric reinforcement direction) with two levels (warp direction and weft direction) and two factors (yarn type and stacking sequence) with three levels (jute/glass, jute/carbon, glass/carbon and consecutive, low strength inside, high strength inside) are selected as the reinforcement design. Full factorial experimental design analysis results indicate that, the highest tensile and impact strength values among the experimental design are realised when samples are taken from the warp direction and E-glass/carbon combination is chosen as the yarn (material) type. Moreover, it is verified that while higher tensile strength is achieved by placing higher strength fabrics to the inner layers, higher impact strength is achieved by placing high strength fabrics to the outer layers of hybrid composite structures. Analysis of variance tables also show that at 95% confidence level, the effects of the factors are statistically significant ( p < 0.05).